HARGA SAHAM PERUSAHAAN SUB SEKTOR FARMASI DAN FAKTOR YANG MEMPENGARUHINYA - Leonaldi Hutajulu; Jhonni Sinaga; Supriyanto (BORJUIS: JURNAL OF ECONOMY, 2024)
A This study aims to analyze the effect of financial ratios on stock prices. In this study, fi-nancial ratios were used, namely Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Equity (ROE). The data analysis method used is descriptive statistics, classical assumption test, multiple linear regression, and hypothesis testing. The results of this study conducted partially show that CR and DER while ROE have no effect on the share price of pharmaceutical sub-sector companies listed on the IDX for the 2018-2022 period. Meanwhile, the results of research conducted simultaneously show that CR, DER, and ROE have an effect on the share price of the pharmaceutical sub-sector companies listed on the IDX for the 2018- 2022 period.